Teacher candidates' and course instructors' perspectives of a mandatory Indigenous Education course in teacher education - Melissa Oskineegish; Paul Berger (Brock University, 2021)
This mixed methods study examined non-Indigenous teacher candidates' disposition towards a mandatory Aboriginal Education course in teacher education from teacher candidates' and course instructors' perspectives. Results from a pre- and post Likert Scale survey of two sections of an Aboriginal Education course at a small Canadian University indicated that teacher candidates felt more knowledgeable by the end of the course, and maintained a fairly strong interest in, and positive attitude towards, the course. Results from course instructors provided additional and, at times, contradictory information, describing the course as limited and, at best, an introduction to the issues and perspectives within Indigenous education. The results suggest the need for mandatory Indigenous Education courses and for faculties of education and school boards to provide further learning opportunities with Indigenous education content and resources.